PERAN POLA ASUH OTORITER TERHADAP KEMATANGAN EMOSI YANG DIMODERATORI OLEH KESABARAN - El Hafiz, Subhan; Almaududi, Abul A’la (Universitas Ahmad Dahlan, 2015)
AbstractAuthoritarian Parenting style often judged as disturbing parenting style for development of the children. However, some of research shown inconsistency which is the parenting style also could give positive impact or have no effect. The purpose of this research was to exlpore the role of authoritarian parenting style to the development of the emotional maturity that expected to be moderated by patience competency. Participants of this research were 200teenagers, 119 female and 81 male, who are study in Senior High School in Jakarta. Data was collected by Patience Competency questionnaire, Emotional Maturity questionnaire and Parental Authority Questionnaire (PAQ). Data was analyzed through a moderator analysis. The result showed that the patience competency does not significat play as moderator variable to the authoritarian parenting style and teenager’s emotional maturity. Futher analysis has proven that authoritarian parenting style and patience competency that was conducted by mother might gave positive impact to teenager’s emotional maturity. Keywords: authoritarian parenting style, emotional maturity, patience